2016
DOI: 10.1016/j.techfore.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Cost–benefit analysis of applied research infrastructure. Evidence from health care

Abstract: The present study aims at offering empirical evidence to improve existing knowledge and theory building on research infrastructure evaluation. Through an inductive case study research strategy, an innovative cost-benefit analysis framework has been used to assess the impact of an applied research infrastructure. The case study is the National Hadrontherapy Centre for Cancer Treatment (CNAO) located in Pavia (Italy). CNAO is an applied research facility specialised in hadrontherapy, an advanced oncological trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Important insights are also offered by Salter and Martin (2001); for a more general discussion see Stephan (1996) and Price (1984). For qualitative case studies, see inter alia Fahlander (2016) on the impact of two accelerators (HIE-ISOLDE and ESS) on local firms, Pero (2013) on three accelerators for material science (Elettra Synchrotron in Trieste, ESRF synchrotron in Grenoble, and XFEL in Hamburg), and OECD (2014) with a specific focus on LHC magnets, a core feature of the accelerator that is discussed in some detail by Rossi and Todesco (2009), and hadron therapy (Battistoni et al, 2016).…”
Section: Public Procurement and Innovationmentioning
confidence: 99%
“…Important insights are also offered by Salter and Martin (2001); for a more general discussion see Stephan (1996) and Price (1984). For qualitative case studies, see inter alia Fahlander (2016) on the impact of two accelerators (HIE-ISOLDE and ESS) on local firms, Pero (2013) on three accelerators for material science (Elettra Synchrotron in Trieste, ESRF synchrotron in Grenoble, and XFEL in Hamburg), and OECD (2014) with a specific focus on LHC magnets, a core feature of the accelerator that is discussed in some detail by Rossi and Todesco (2009), and hadron therapy (Battistoni et al, 2016).…”
Section: Public Procurement and Innovationmentioning
confidence: 99%
“…Autio et al (2014), based on three in depth case-studies, found innovation benefits accruing to the firms involved by CERN through prototypes' mocking up and experimentation. Closely related contributions are those by Amaldi (2012), Nielsen and Anelli (2016), and Battistoni et al, (2016) highlighting that thanks to the collaboration with CERN several firms were subsequently able to develop new products for customers in other markets.…”
Section: Brief Literature Review On the Economic Effects Of Cern Procmentioning
confidence: 90%
“…There is a wide range use of BCR in measuring the feasibility of the project or program including health [8][9][10], natural resources management [11,12], and renewable energy from wind power [13]. Thus, it is expected that the combination of the application FA and CBA in this study may provide comprehensive analysis and may also provide broad policy recommendation.…”
Section: Cost and Benefit Analysismentioning
confidence: 99%